PENGARUH DISIPLIN KERJA, KOMITMEN ORGANISASI, DAN MOTIVASI KERJA, TERHADAP KINERJA BINTARA DINASPERSONEL PANGKALAN TNI ANGKATAN UDARA ADISUTJIPTO - Yunus, Mochammad; Dirwan, A (Prodi Magister Manajemen Universitas Dirgantara Marsekal Suryadarma, 2025)
This research aims to analyze the influence of work discipline, organizational commitmentand work motivation on the performance of non-commissioned officers at the AdisutjiptoAir Force Base. This research uses a quantitative approach, surveymethodsand pathanalysis.The populationwas89people,with a saturated sampling technique obtained 89respondents. Data were analyzed using Excel and SPSS version 25. The results showedthat: Work discipline had a direct positive and significant effect on work motivationof0.381;Organizationalcommitment hasadirectpositiveand significanteffectonworkmotivationof0.427;Workdisciplinehasadirect positive and significant effect on performance of0.460; Organizational commitmenthasadirectpositiveandsignificanteffectonperformanceof0.369; Work motivation has a direct positive and significant effect on theperformance of Adisutjipto Air Force Dispersal Non-Commissioned Officers at 0.252.